Factors Influencing Stress in Mothers Experiencing Domestic Violence: Scoping Review - Indah Qolbiyati; Meidiana Dwidiyanti; Luky Dwiantoro (GLOBAL HEALTH SCIENCE GROUP, 2024)
Domestic violence is a violation of human rights, a crime against human dignity and a form of discrimination. Violence, whatever the form or reason, is a form of crime that cannot be justified. Domestic violence is a global problem and a serious public health problem throughout the world. According to several scientific studies, risk factors for domestic violence include young age, desire to have children, pregnancy, separation from a partner, low socio-economic status, low education level, unemployment, drug abuse, social and economic inequality, among others. Objectives: Concluding on the factors that influence stress in mothers who experience domestic violence. Method: This article uses three data based science direct, scopus and wiley. The search for this article uses the main keywords, namely factors and and stress and mother and domestic violence combined with supporting keywords, the article is in full text form, in English, limited to the last 5 years and open access as many as 10 articles were reviewed. Result: This review was carried out on 10 articles that were screened and analyzed from 2,801 articles. All articles use qualitative, quantitative and Multivariate logit models, moderation and mediation analysis methods. Factors that influence the level of stress in mothers who experience domestic violence are physical and emotional violence.Conclusion: Emphasizing that handling stress in mothers who experience domestic violence requires a comprehensive approach, involving various sectors, including health, education and social policy. By understanding the factors that influence stress, more effective intervention efforts can be designed and support women in overcoming traumatic experiences of domestic violence.